Effect of Performance Assessment on Employee Motivation in Hotel X Bandung - Subakti, Agung Gita (Bina Nusantara University, 2010)
The success of an organization comes from the ability of employees to meet performance standards that have been made by the management of operational activities to be running well. Therefore, knowing how well the employees performance is a must for the management. A tool used to determine how well the employees performance is by conducting a performance appraisal. The performance evaluation is one tool used by hotels or other business types to evaluate the performance of employees and also as a tool to motivate the employee. With a good performance assessment will produce a form of accurate data regarding the advantages and disadvantages of the employees and also will motivate employees to perform their tasks.Â